1985
DOI: 10.1111/j.1524-4725.1985.tb01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Squamous‐Cell Carcinomas Derived from Solar Keratosis

Abstract: Actinic squamous-cell carcinoma has been described to have a low risk of metastasis. Reported here are four Japanese cases of lymphatic metastasis of squamous-cell carcinoma derived form solar keratosis. The primary lesions were on the face in three cases and on the back of the hand in one. Two patients died, and others had recurrent incurable metastatic lymph nodes. Therefore, it is noteworthy that actinic squamous-cell carcinoma in the Japanese can become so aggressive and metastasize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 14 publications
0
10
1
1
Order By: Relevance
“…Their histologic analysis revealed that one of the lesions arose in a hypertrophic AK. 24 In our analysis, hypertrophic AKs were not seen more frequently in treatment-resistant patients, although differences in the overall histologic thickness of the epidermis between case and control patients approached statistical significance, with a trend toward a thicker overall epidermis being seen in case patients. A similar trend was not seen with thickness of the atypical portion of the epidermis measured in millimeters or layers or in the number of atypical mitotic figures (Table 3).…”
Section: O N D O E T a Lcontrasting
confidence: 45%
See 1 more Smart Citation
“…Their histologic analysis revealed that one of the lesions arose in a hypertrophic AK. 24 In our analysis, hypertrophic AKs were not seen more frequently in treatment-resistant patients, although differences in the overall histologic thickness of the epidermis between case and control patients approached statistical significance, with a trend toward a thicker overall epidermis being seen in case patients. A similar trend was not seen with thickness of the atypical portion of the epidermis measured in millimeters or layers or in the number of atypical mitotic figures (Table 3).…”
Section: O N D O E T a Lcontrasting
confidence: 45%
“…Fukamizu and colleagues reported on four cases of metastasis arising from a cutaneous primary SCC. Their histologic analysis revealed that one of the lesions arose in a hypertrophic AK . In our analysis, hypertrophic AKs were not seen more frequently in treatment‐resistant patients, although differences in the overall histologic thickness of the epidermis between case and control patients approached statistical significance, with a trend toward a thicker overall epidermis being seen in case patients.…”
Section: Discussionmentioning
confidence: 47%
“…65 This finding is consistent with similar findings for SCC of the skin with AK, and sporadic BCC with solar elastosis. 8,50,57,65,[132][133][134][135][136] It has long been suggested that lip SCC derived from SC has a significant malignant potential. 137 However, recent evidence suggests that SCC originating from or associated with SC is approximately three to five times less likely to metastasize than lower lip SCC that is not derived from or associated with SC.…”
Section: Disease Course Key Pointsmentioning
confidence: 99%
“…On cytological grounds alone, AK and SCC are indistinguishable 5 . Both contain atypical keratinocytes with loss of polarity, nuclear pleomorphism, disordered maturation, and increased numbers of mitotic figures, many of them atypical and pleomorphic 6 .…”
Section: Histopathologymentioning
confidence: 99%